Optimization of Airway Clearance in Pulmonary Tuberculosis Patients Through Chest Physiotherapy and Effective Cough Training: A Case Report - Winanda Diany; Rycco Darmareja (Jurnal Keperawatan Duta Medika, 2026)
Introduction: Pulmonary tuberculosis remains the leading cause of death globally. Many programs have been launched by the government, but the prevalence remains high. Ineffective airway clearance is one of the nursing problems that interfere with oxygenation needs.Objectives:  This study aims to identify the optimization of airway clearance status in patients with pulmonary TB through the application of chest physiotherapy interventions and effective cough training.Methods:  A case study was conducted on selected pulmonary tuberculosis patients, based on the criteria set by the researcher. Data were collected through interview procedures, physical and supporting examinations, observation and review of patient medical records. The application of evidence based practice in the form of chest physiotherapy and effective cough training was observed in depth for five days of treatment to assess optimization of the patient's airway clearance indicators and then recorded on the observation sheet provided.Results:  After the intervention, it was found that there was a decrease in respiratory frequency (towards normal), a decrease in the scale of tightness (towards improvement), a decrease in areas with abnormal breath sounds, and an improvement in the patient's sputum characteristics.Conclusions:  It is concluded that there is an effect of chest physiotherapy and effective cough training on improving indicators of airway clearance disorders.  The author hopes that nurses can optimize the application of this intervention as an airway clearance management strategy for patients with pulmonary Tb.Keyword:  chest physiotherapy, case study, effective cough, pulmonary tuberculosis Pendahuluan: Tuberkulosis paru masih menjadi penyebab kematian tertinggi global. Banyak program yang dicanangkan pemerintah, namun prevalensinya masih tetap tinggi. Bersihan jalan napas tidak efektif menjadi salah satu masalah keperawatan yang mengganggu kebutuhan oksigenasi.Tujuan: Studi ini bertujuan untuk mengidentifikasi optimalisasi status bersihan jalan napas pada pasien TB paru melalui penerapan intervensi fisioterapi dada dan latihan batuk efektif.Metode: Studi deskriptif kualitatif berupa case study di lakukan pada pasien Tb Paru terpilih, berdasarkan kriteria yang ditetapkan peneliti. Data di kumpulkan melalui prosedur wawancara, pemeriksaan fisik dan penunjang, observasi serta kajian pada rekam medis pasien. Penerapan evidance based practice berupa fisioterapi dada dan latihan batuk efektif di observasi mendalam selama lima hari perawatan untuk menilai optimalisasi pada indikator bersihan jalan napas pasien kemudian di catat pada lembar observasi yang disediakan.Hasil: Setelah dilakukan intervensi diperoleh hasil bahwa terjadi penurunan frekuensi napas (ke arah normal), penurunan skala sesak (ke arah perbaikan), penurunan area dengan suara napas abnormal, serta perbaikan karakteristik sputum pasien.Kesimpulan:  Terdapat pengaruh fisioterapi dada dan latihan batuk efektif terhadap perbaikan indikator gangguan bersihan jalan napas. Penulis berharap perawat dapat mengoptimalkan penerapan intervensi ini sebagai strategi manajemen bersihan jalan napas pasien Tb paru.Kata Kunci:  batuk efektif, fisioterapi dada, studi kasus, tuberkulosis paru